Development and maturation of the fibrous components of the arterial roots in the mouse heart. Issue 4 (15th October 2017) - Richardson, Rachel; Eley, Lorraine; Donald‐Wilson, Charlotte; Davis, Jonathon; Curley, Natasha; Alqahtani, Ahlam; Murphy, Lindsay; Anderson, Robert H.; Henderson, Deborah J.; Chaudhry, Bill
Abstract: The arterial roots are important transitional regions of the heart, connecting the intrapericardial components of the aortic and pulmonary trunks with their ventricular outlets. They house the arterial (semilunar) valves and, in the case of the aorta, are the points of coronary arterial attachment. Moreover, because of the semilunar attachments of the valve leaflets, the arterial roots span the anatomic ventriculo‐arterial junction. By virtue of this arrangement, the interleaflet triangles, despite being fibrous, are found on the ventricular aspect of the root and located within the left ventricular cavity. Malformations and diseases of the aortic root are common and serious. Despite the mouse being the animal model of choice for studying cardiac development, few studies have examined the structure of their arterial roots. As a consequence, our understanding of their formation and maturation is incomplete. We set out to clarify the anatomical and histological features of the mouse arterial roots, particularly focusing on their walls and the points of attachment of the valve leaflets. We then sought to determine the embryonic lineage relationships between these tissues, as a forerunner to understanding how they form and mature over time. Using histological stains and immunohistochemistry, we show that the walls of the mouse arterial roots show a gradual transition, with smooth muscle cells (SMC) forming the bulk of wall at the most distal points of attachments of the valve leaflets, while being entirely fibrous at their base. Although the interleaflet triangles lie within the ventricular chambers, we show that they are histologically indistinguishable from the arterial sinus walls until the end of gestation. Differences become apparent after birth, and are only completed by postnatal day 21. Using Cre‐lox ‐based lineage tracing technology to label progenitor populations, we show that the SMC and fibrous tissue within the walls of the mature arterial roots share a common origin from the second heart field (SHF) and exclude trans‐differentiation of myocardium as a source for the interleaflet triangle fibrous tissues. Moreover, we show that the attachment points of the leaflets to the walls, like the leaflets themselves, are derived from the outflow cushions, having contributions from both SHF‐derived endothelial cells and neural crest cells. Our data thus show that the arterial roots in the mouse heart are similar to the features described in the human heart. They provide a framework for understanding complex lesions and diseases affecting the aortic root.